Vaccination to Prevent Pseudomonas aeruginosa Bloodstream Infections - Hart, Robert J.; Morici, Lisa A. (Frontiers in Microbiology, 2022)
The bacterium Pseudomonas aeruginosa (Pa) is ubiquitous in the environment and causes opportunistic infections in humans. Pa is increasingly becoming one of the most difficult to treat microorganisms due to its intrinsic and acquired resistance to multiple antibiotics. The World Health Organization estimates that at least 700,000 people die each year from drug resistant microbial infections and have listed Pa as one of three bacterial species for which there is the most critical need for the development of novel therapeutics. Pa is a common cause of bloodstream infections (BSI) and bacterial sepsis. With nearly 49 million sepsis cases and 11 million deaths worldwide, an effective vaccine against Pa could prevent the morbidity and mortality resulting from Pa BSI and lessen our dependence on antibiotics. We reviewed the current landscape of Pa vaccines in pre-clinical and clinical stages over the last two decades. It is readily apparent that Pa vaccine development efforts have been largely directed at the prevention of pulmonary infections, likely due to Pa’s devastating impact on individuals with cystic fibrosis. However, the increase in nosocomial infections, BSI-related sepsis, and the emergence of widespread antibiotic resistance have converged as a major threat to global public health. In this perspective, we draw attention to potential Pa vaccine candidates and encourage a renewed effort for prophylactic vaccine development to prevent drug-resistant Pa BSI.